Survey Of Islamic Art In The Holy Shrine Of Ghasem (As) Ureh In The Damavand City Of Tehran Province - Youzbashi, Atieh; Emamifar, Seyed Nezam Oldin (The Turkish Online Journal of Design Art and Communication, 2016)
Islamic art or the arts of Muslims is a part of art in Muslim society and not necessarily by Muslims. Although in some cases, this arts may not go with the ethics and rules of Islam. The impact of Islamic and regional culture in this arts is obvious. Islamic art is not an art that is only related to Islam. The “Islamic” does not only refer to the religion but also it refers to the rich culture and different types of people who live in Islamic lands. Familiarity with Islamic art in the shrines and the pictorial motifs in them leads to getting familiar with semiology. Arts used in the shrines are one of the most obvious representatives of Islamic culture and spiritual atmosphere. The way of doing the research is based upon the descriptive and analytic nature, and the way of compiling information is combined. The way of taking sample is not random (Chosen) and the way of interpreting and analyzing the information is both qualitative. Initially in this research, the basic of Islamic art are introduced and then the example of Islamic art in the shrine of Ghasem (AS) which include, wood carving, fretwork, girih tile, illumination and reticulated metal. Motifs and signs and other features are shown in tables and diagrams and one motif is analyzed semiologically. Getting the meaning and understanding the patterns and motifs necessitate deep study. This essay is to consider pictorial motifs, religious beliefs and symbolic meaning in the Islamic art. In the Islamic art, we faced the repeated elements, like; the use of geometric patterns or non-realistic drawing of a flower or plant that is called arabesque. Arabesque motifs in Islamic art are often used as the symbol of a very vast universe which is created by God. Deliberation in not showing and imitating nature exactly is said to be as a sign of the modesty of the artists who believe, creation of perfection is just for god, as a result in the motifs and decoration of Damavand shrine, the flowers and plants that are specific for that region is not used.
Keywords: Islamic art; shrine; Damavand city; the shrine of Ghasem Keywords: (AS) Ureh; Semiology